Manual de importación de la empresa Insuelmar para los productos de melaza y silicato. - Niebla Campoverde, Darwin Vladimir (Machala : Universidad Técnica de Machala, 2022)
This titling project is based on the design and implementation of an import process for the company “INSUELMAR C. Ltd.”. In the city of “Machala”, Province of “El Oro” in the year 2022. To carry out this process, it is important to use the knowledge and resources learned in the Career of “Comercio Exterior”, in addition to the analysis of the field of action chosen, detailed and exposed in this work, actions that are part of the solution of the problem that the aforementioned company is going through, emphasizing that although its main activity is the commercialization of inputs for the aquaculture activity, especially molasses and silicate, the profit margin is not adequate due to the negotiations to obtain the products that are carried out through outsourcing. What is expected to be achieved is that INSUELMAR generates greater competitiveness and positioning in the current market, which will allow increasing the economic support of its partners. For the proposal of the process, the necessary requirements that a company that needs to be a direct importer must have been met, taking advantage of the human and material resources that INSUELMAR currently has, within the framework of legislation established in Ecuador. Finally, the import process is implemented, the result of which is measured by surveys and interviews directed at consumers, workers and owners, respectively.
El presente proyecto de titulación se basa en el diseño e implementación de un proceso de importación para la Empresa INSUELMAR C. Ltda. En la ciudad de Machala Provincia de El Oro en el año 2022. Para efectuar dicho proceso es importante la utilización de los conocimientos y recursos aprendidos en la Carrera de Comercio Exterior, además del análisis del campo de acción de escogido, detallado y expuesto en este trabajo, acciones que forman parte de la solución de la problemática que atraviesa la empresa citada, recalcando que aunque su actividad principal sea la comercialización de insumos para la actividad acuícola especialmente melaza y silicato, el margen de ganancia no es el adecuado debido a las negociaciones para la obtención de los productos que se efectúa mediante tercerización. Lo que se espera conseguir es que INSUELMAR genere mayor competitividad y posicionamiento en el mercado actual, que permitan incrementar el sustento económico de sus socios. Para la propuesta del proceso se ha reunido los requisitos necesarios que debe poseer una empresa que requiera ser importadora directa, aprovechando los recursos humanos y materiales que actualmente INSUELMAR ostenta, dentro del marco de legislación establecido en el Ecuador. Finalmente se implanta el proceso de importación, cuyo resultado es medido por encuestas y entrevistas dirigidas a los consumidores, trabajadores y dueño respectivamente.
Keywords: PROCESO; IMPORTACION; ACTIVIDAD COMERCIAL; SILICATO